2017
DOI: 10.1007/s11064-017-2281-1
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Stomach–Brain Interaction Induced by Molecular Hydrogen in Parkinson’s Disease Model Mice

Abstract: Molecular hydrogen (H), as a new medical gas, has protective effects in neurological disorders including Parkinson's disease (PD). In our previous report, the neuroprotective effect of drinking water with saturated H (H water) in PD mice might be due to stomach-brain interaction via release of gastric hormone, ghrelin. In the present study, we assessed the effect of H-induced ghrelin more precisely. To confirm the contribution of ghrelin in H water-drinking PD model mice, ghrelin-knock out (KO) mice were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Both SDV and SDA are well-established techniques in rat, however, there are less studies using these techniques in mouse models. Mice undergoing bilateral SDV have been shown to survive for at least two weeks post-surgery (Iwasaki et al, 2015;Yoshii et al, 2017). However, a study has reported the lethality of this procedure in mice due to gastric distension and pyloric stenosis (Dezfuli et al, 2018).…”
Section: Surgical-based Approachesmentioning
confidence: 99%
“…Both SDV and SDA are well-established techniques in rat, however, there are less studies using these techniques in mouse models. Mice undergoing bilateral SDV have been shown to survive for at least two weeks post-surgery (Iwasaki et al, 2015;Yoshii et al, 2017). However, a study has reported the lethality of this procedure in mice due to gastric distension and pyloric stenosis (Dezfuli et al, 2018).…”
Section: Surgical-based Approachesmentioning
confidence: 99%
“…22 However, the mechanism appears more complicated since the protective effects of HRW were still observed in a ghrelin-KO mice model of Parkinson's disease. 23 Nevertheless, it appears that a higher concentration of H 2 is at least as effective as, and often more effective than, a lower H 2 concentration. For example, it has been demonstrated that high-concentration hydrogen produced via magnesium was more effective than lowconcentration H 2 contained in alkaline ionized water in attenuating non-alcoholic fatty liver disease (NAFLD) in mice fed a high-fat diet.…”
Section: Introductionmentioning
confidence: 98%
“…In a rat model of subarachnoid hemorrhage, injection of H 2 saline inhibits the nuclear factor-kappa B pathway and the nucleotide binding and oligomerization domain-like receptor family pyrin domain–containing three inflammasomes, which subsequently reduces the systemic inflammatory response and promotes the neurological function, as well as behavioural recovery 31. Yoshii et al38 reported that the observed neuroprotective effect of drinking hydrogen water could be associated with the secretion of ghrelin, a gastric hormone, in the stomach. However, the mechanism of H 2 appears to differ between the various experimental models.…”
Section: Hydrogenmentioning
confidence: 99%